2020
DOI: 10.1177/1461444820958717
|View full text |Cite
|
Sign up to set email alerts
|

Social media, rituals, and long-distance family relationship maintenance: A mixed-methods systematic review

Abstract: For families with limited opportunities for face-to-face interaction, social media can be a vital communication medium to help shape the family identity, maintain bonds, and accomplish shared tasks. This mixed-methods systematic review of quantitative, qualitative, and mixed-method empirical studies published between 1997 and 2019 uses a convergent data-based framework to explore how long-distance families engage in family practices using various modes of social media. Fifty-one papers were synthesized into fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 88 publications
(274 reference statements)
0
39
0
1
Order By: Relevance
“…Legitimization is particularly prominent in the well-established social-media ritual (Abel, Machin, and Brownlow 2020) where users lend approval to each other's personal desires. In the social displaying of a trip to this or that destination, the purchase of this or that commodity, and so forth, producers of status updates justify their lifestyle to their assumedly understanding followers/friends or are fishing for emotional or rational support for it.…”
Section: Reificationmentioning
confidence: 99%
“…Legitimization is particularly prominent in the well-established social-media ritual (Abel, Machin, and Brownlow 2020) where users lend approval to each other's personal desires. In the social displaying of a trip to this or that destination, the purchase of this or that commodity, and so forth, producers of status updates justify their lifestyle to their assumedly understanding followers/friends or are fishing for emotional or rational support for it.…”
Section: Reificationmentioning
confidence: 99%
“…Reviews on the use of ICT for social contact by the elderly (e.g., k = 25, Chen & Schulz, 2016;k = 34, Fan, 2016) and the general population (e.g, Abel et al, 2020, k = 51) included more studies.…”
Section: Discussionmentioning
confidence: 99%
“…The use of video conferencing by people with mild-to-moderate intellectual disabilities was briefly mentioned by one study (Ramsten et al, 2019), but no further details were reported. The modes of communication described in the included studies are also used by the general population (e.g., van den Berg et al, 2012) and by long-distance families who do not have regular in-person contact (Abel et al, 2020;Wilding, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research investigating long-distance relationships has indicated that communication via technology can be a viable alternative for relationship maintenance instead of face-to-face interaction (Abel et al, 2020;Belus et al, 2018). However, the important difference between COVID-19 lockdown and more traditional technology-based relationships is that lockdown can create an abrupt, unplanned, and non-voluntary shift of some or all relationships that were primarily maintained faceto-face, to technology-based.…”
Section: The Potential Impact Of Covid-19 Lockdown On Social Relationmentioning
confidence: 99%